Exploring the potential of plant-derived natural products beyond functional food: Applications in nanomedicine - Luna Criado, Carlos; Mendoza Reséndez, Raquel (MedCrave, 2015)
The use of plant products as nutritional food and therapeutic agents is immemorial and intimately linked to the human life since its origin. Also, the tanning action of plant extracts has been hugely exploited to transform animal skins into leather from ancient times to present. However, the exploitation of the potential applications of the plant biomolecules in some of the modern technologies is rather now emerging. In fact, the power antioxidant, reducing and biological activities of the plant metabolites, together their chelating and their biodegradable properties, make the plant-derived natural products unique raw materials to design new sustainable approaches to prepare promising hybrid formulations and composites at the nanometer scale for innovative diagnostic and therapeutic procedures and nanotechnology applications. In the present contribution, some recent advances in this topic are briefly discussed.